Development of a Rapid On-Site Method for the Detection of Chicken Meat in Processed Ground Meat Products by Using a Direct Ultrafast PCR System - Sul, Suyeon; Kim, Mi-Ju; Lee, Jung-Min; Kim, Sung-Yeon; Kim, Hae-Yeong (Journal of food protection, 2020)
In this study, we developed a rapid on-site detection method by using direct ultrafast PCR coupled with a microfluidic chip to identify the presence of chicken meat in processed ground meat products. Chicken-specific PCR primer targeting mitochondrial 16S rRNA gene was newly designed, and its specificity was confirmed against 17 other animal species and 4 different chicken meat samples from different countries of origin. The sensitivity of the chicken-specific ultrafast PCR was 0.1 pg of chicken DNA. To evaluate the limit of detection of the direct ultrafast PCR method, different percentages of chicken meat mixed with pork or beef were prepared. The limit of detection of the direct ultrafast PCR method for the chicken meat-pork and chicken meat-beef mixtures was 0.1% for both raw meat and autoclaved meat. This method was used for 15 commercialized processed ground meat products. In this method, the target sequence was successfully amplified, and the presence of chicken meat in processed ground meat products was identified within approximately 25 min, including the time for sample preparation. Thus, our study shows that this developed direct ultrafast PCR method is a rapid and accurate method for on-site detection of chicken DNA in commercial food products.